Dynamic Susceptibility of Permalloy Wire-Tube Nanostructures - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2021)
In this work, we have theoretically explored the spin-waves modes that can be excited in cylindrical nanostructures with wire-tube morphology. Using micromagnetic simulations, we have found up to 5 resonance modes whose existence and position depend on the geometric parameters of the nanostructure. The lower and higher frequency modes remain invariant in their position as a function of the size of the tube segment hole, although their intensity increases as the length of the wire segment increases. Other modes vary in their frequency, even producing a crossover between them. Finally, we found that the number and amplitude of the reported spin-wave modes have a complex dependence on the geometry of the system, converting the wire-tube nanostructure into a promising piece for potential magnonic devices. © 2021 The Authors